The Strategic of Managerial Supervision in The Forming of the Madrasah Work Plan - Rudi Ahmad Suryadi (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2018)
The quality of madrasah management is supported by good planning. The Madrasah Work Plan is one of the aspects related to the development of national education standards of it. In the context of supervision, it is part of the madrasah managerial. Madrasah supervisors in this case can develop appropriate strategies to provide guidance in planning development. Some strategies that can be developed are monitoring and evaluation, focused group discussion (FGD), delphie methods, and billings.